Utilization of Color Space Value Filter for Laser Pointer Spot Detection with a Single Board Computer - julham -; Hikmah Adwin Adam; Meryatul Husna (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
A color space is an abstract mathematical model that describes how a color can be represented as a row of numbers. One abstract mathematical model of the color space that represents the brightness of a color is the value color space or known as the value filter. For this reason, a gray scale is used with a value range of 0 to 255. This is tested in detecting a red laser pointer light spot that is directed into a field. The results obtained show that more inconsistent detection results are displayed than consistent detection results (can be seen in table 1 and table 2). This can happen because the area of the image captured by the camcorder has several pixels with a maximum gray level value or a gray level value that exceeds the specified limit value (maxBri variable).